Microplastic Depuration on Asaphis Detlorata - Saputri, Dian Fatriani Indah; Daud, Anwar; Syah, Rachman; Birawida, Agus Bintara; Amqam, Hasnawati; Russeng, Syamsiar S. (International Journal Papier Advance and Scientific Review, 2020)
Depuration is an effort to reduce/eliminate contamination including microplastics, which one is using a water circulation system. This study aims to determine the effective depuration time to reduce the microplastic content in Asaphis detlorata This study used a quantitative approach with experimental research design with a completely randomized design. There are 450 shells used as an experimental animal where is the treatment consisted of four depuration times, namely 1;2;3; and 4 days with 3 repetitions of each treatment, while the control shells were without depuration. Analysis of variance (ANOVA) was used to see the effect of depuration treatment on the microplastic content. If the effect of the treatment was significantly different, then the post hoc test was continued to determine the differences between treatments. The results showed that Asaphis detlorata obtained from the mouth of the Lakatong river estuary were contaminated with microplastics ranging from 0.6 to 8.1 MPs/shellfish and an average of 3.96 MPs/shellfish. Depuration time significantly affected the microplastic content in shellfish depuration effectiveness. There is a tendency that the longer depuration time is decreased microplastic content in shellfish. The effective depuration time to reduce the microplastic content in Asaphis detlorata was 3 and 4 days. Further research is needed for a more effective depuration for cleaning microplastics in shellfish.